2007
DOI: 10.1111/j.1468-036x.2007.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisitions, Overconfident Managers and Self‐attribution Bias

Abstract: "We examine whether acquisitions by overconfident managers generate superior abnormal returns and whether managerial overconfidence stems from self-attribution. Self-attribution bias suggests that overconfidence plays a greater role in higher order acquisition deals predicting lower wealth effects for higher order acquisition deals. Using two alternative measures of overconfidence (1) high order acquisition deals and (2) insider dealings we find evidence supporting the view that average stock returns are relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
183
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(221 citation statements)
references
References 100 publications
(180 reference statements)
24
183
1
6
Order By: Relevance
“…Results are in line with those of Choi and Dong (2008) and also Doukas and Petmezas (2007). Self-Attribution Bias can be particularly problematic in times of rising stock prices.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Results are in line with those of Choi and Dong (2008) and also Doukas and Petmezas (2007). Self-Attribution Bias can be particularly problematic in times of rising stock prices.…”
Section: Discussionsupporting
confidence: 72%
“…Overconfidence leads to investing in industries which are not in the circle of competence of those investors. Doukas and Petmezas (2007) also find a relationship between Self-Attribution Bias and Overconfidence for institutional investors. Overconfidence leads to excessive trading, which is responsible for poor investment results (Doukas & Petmezas, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Our results, which are not presented for brevity, are qualitatively similar and are available upon request. 13 This result is in line with the evidence of Chang (1998), Fuller, Netter andStegemoller (2002) and Doukas and Petmezas (2007) who document substantial gains in acquisitions of privately held firms. Consistent with the U.S. evidence, U.K. studies (Draper and Paudyal (2006), among others) report negative and significant bidder abnormal returns for public acquisitions surrounding merger announcements.…”
Section: Acquirer Announcement Returns and Market Valuations: Univarisupporting
confidence: 81%
“…In the case of M & A investment, Malmendier U et al [7] and Doukas J.A. [8] found that the over-confident CEOs have a higher probability than that of non-over-confident CEOs in the M & A investment , and paid higher prices, obtain Lower yields, which will finally damage the corporate benefits [9] [10] [11].…”
Section: Literature Reviewmentioning
confidence: 99%